(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Introduction. Chiari malformation type 1 (CM1) is a congenital disorder whose clinical manifestations typically occur in young individuals of working age. The disease is characterized by a wide range of clinical manifestations, including CM1-associated headaches, syringomyelia, otoneurological disorders, and ataxia, primarily caused by impaired cerebrospinal fluid flow at the cerebrospinal junction. However, asymptomatic carriage of the posterior cranial fossa phenotype characteristic of CM1 is also possible. CM1 leads to a decrease in quality of life and difficulty in everyday and professional activities in more than 90% of clinically symptomatic patients, and also causes disability [1-3]. The literature primarily presents data on disability associated with CM1-associated syringomyelia. The relationship between isolated CM1 and the development of disability has been insufficiently addressed. The potentially disabling effect of MC1, combined with the presence of areas with a high prevalence of this pathology, including the Volga-Kama region [1, 4-6], all this testifies to the important social significance of the pathology in question and the relevance of studying disability in MC1. According to the literature, syringomyelia is detected in Chiari malformation with a frequency of 43 to 87% [1, 2]. The relationship between Chiari malformation and syringomyelia has been discussed by specialists since the 1950s [3, 4]. Chiari malformation is a displacement of the cerebellar tonsils (ectopia) through the foramen magnum to the level of the C1, sometimes C2I-C3I vertebrae. Many authors believe that this is the only pathological condition in such pathology, while at the same time there are studies that claim that the initial cause is the small volume of the posterior cranial fossa (PCF), which causes the displacement of the cerebellar tonsils downwards through the foramen magnum [5, 6].